2015
DOI: 10.1093/bja/aeu458
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intraoperative hypotension and blood pressure fluctuations on early postoperative delirium after non-cardiac surgery

Abstract: These results showed that increased blood pressure fluctuation, not absolute or relative hypotension, was predictive of postoperative delirium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
91
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(107 citation statements)
references
References 71 publications
5
91
1
1
Order By: Relevance
“…Blood pressure elevation is the strongest risk factor for dementia, if the intraoperative pressure is not controlled well, a stroke might consequently occur would further worsen cognitive derangement (20). Hirsch et al have previously reported, increased blood pressure fluctuation, not absolute or relative hypotension was predictive of postoperative delirium (21). So we speculate that postoperative delirium can be decreased by less cardiovascular stress response during anesthesia and maintaining the hemodynamic stability during the preoperative periods in patients with a history of hypertension.…”
Section: Discussionmentioning
confidence: 71%
“…Blood pressure elevation is the strongest risk factor for dementia, if the intraoperative pressure is not controlled well, a stroke might consequently occur would further worsen cognitive derangement (20). Hirsch et al have previously reported, increased blood pressure fluctuation, not absolute or relative hypotension was predictive of postoperative delirium (21). So we speculate that postoperative delirium can be decreased by less cardiovascular stress response during anesthesia and maintaining the hemodynamic stability during the preoperative periods in patients with a history of hypertension.…”
Section: Discussionmentioning
confidence: 71%
“…In several patient populations, prolonged periods of hypotension have been associated with poorer outcomes . The constraints of strict fluid management (and in some places, vasopressor avoidance) in free tissue transfer may make hypotension unnecessarily common in these patients .…”
Section: Discussionmentioning
confidence: 99%
“…In several patient populations, prolonged periods of hypotension have been associated with poorer outcomes. [5][6][7][8][9] The constraints of strict fluid management (and in some places, vasopressor avoidance) in free tissue transfer may make hypotension unnecessarily common in these patients. 13 Our study provides evidence that prolonged periods of hypotension are associated with increased risk of flap failure and suggests that part of this increased risk may be mediated through effects other than higher volumes of crystalloid administered in response to hypotension (ie, possibly from hypoperfusion alone).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From my own experience of using similar volumes (1.3 AE 0.3 ml), not only is a small fall predictable, but it tends to occur at a slower rate than with higher volumes, and so avoids 'sawtoothing' of the patient's blood pressure during surgery, with persistent hypotension corrected intermittently with intravenous vasopression. It remains uncertain whether relative or absolute blood pressure values, duration or rate of development of hypotension (or combinations of these) are important in increasingly apparent links between hypotension, mortality and morbidity [4,5], but, as Dr. Tighe points out, intra-operative blood pressure is an anaesthetic problem that would seem to be treatable in part just through the simple action of giving less spinal anaesthetic.…”
mentioning
confidence: 99%